Finance and Development, June 2007. (Finance and Development; Finance and Development, 2007)
The June 2007 issue of F and D spotlights gender equality. The lead article discusses progress toward fulfilling the Millennium Development Goal (MDG) on redressing gender discrimination and empowering women and related MDGs. The section also looks at how budgeting with gender issues in mind can help countries promote gender equality and what needs to be done to get girls from 'excluded' social groups into school. Other articles focus on Asia 10 years after the financial crisis, the implications of China's and India's growing ties with Africa, and making remittances work for Africa. 'Country Focus' looks at the challenges facing Bulgaria now that it has joined the European Union, 'Picture This' highlights the globalization of labor, and 'Back to Basics' gives a primer on microfinance. Two other pieces discuss the efficiency of public spending in Latin America and how countries can use the public sector balance sheet approach to diagnose vulnerabilities that are not immediately visible in the budget.